Meningkatkan Daya Saing UMKM Kuliner dengan Penyuluhan dan Pendampingan Sertifikasi Halal - Hasanah, Erni Ummi; Yumarlin M. Z.; Lantarsih, Retno; Ardi, Iwan Aminto; Kurniawan, Aditya; Anugerah, Nabella Maya (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pamulang, 2025)
This activity aims to increase understanding and assist MSME players in Pleret Panjatan Kulon Progo in obtaining halal certification for their products through counseling and mentoring. This research uses the community service method which was carried out in the Pleret Panjatan Kalurahan Office Hall on September 19, 2024. The activity consists of three stages: planning, counseling, and mentoring. Resource persons from the Ministry of Religious Affairs of Bantul Regency provided material on halal certification and the application process through the SiHalal portal. Assistance is carried out directly to assist MSME players in the process of applying for halal certificates and fulfilling administrative requirements. This activity succeeded in increasing the understanding of culinary MSME players regarding halal certification, as well as motivating them to register their products through the SiHalal portal. In addition, the assistance helps MSME players in fulfilling administrative requirements, such as making a Business Identification Number (NIB), so that they can obtain a halal certificate. The limitation of this research lies in the relatively short implementation time, so that it has not been able to reach all MSME players in Pleret Panjatan Kalurahan as a whole. In addition, limitations in the initial data collection made some potential MSME actors not yet involved in this activity. This activity contributes to increasing the understanding and awareness of MSME actors in coastal areas regarding the importance of halal certification. This activity also makes a practical contribution to the halal certification process through the Free Halal Certificate (Sehati).